Influence of different agroforestry production modules on fine roots biomass in the southeastern Amazon (Research, Society and Development, 2024)
AFS provide important ecosystem services associated with carbon (C) cycling and dynamics and can store C in plant biomass that is often comparable to natural forests. The aim of this study was to quantify and compare the biomass of fine roots (diameter ≤2mm) in different SAF modules (M1, M2, M3, M4, M5) in the southeast of Pará, using two adjacent areas (Urochloa sp. pasture and secondary forest) as a reference. The modules have common crops (banana, manioc, pineapple, corn, cocoa), varying according to the other species intercropped. Each module has an area of 2 ha, the same history and time of implantation, and five 5×5 m plots were randomly installed in each one, where we collected 3 soil samples (0-10 cm) with a volumetric cylinder (196 cm³). In the laboratory, the roots were washed in running water under a 0.5 mm mesh and sorted using tweezers and a caliper. Root biomass was estimated using dry mass (g.m²) and statistical comparisons were made using ANOVA and Tukey's post-test.  Forest and pasture showed greater fine root biomass compared to the SAF modules, which were similar to each other (p